Discovery and Characterization of Biased Allosteric Agonists of the Chemokine Receptor CXCR3. - Lampros, Milanos; Brox, Regine; Frank, Theresa; Poklukar, Gasper; Palmisano, Ralf; Waibel, Reiner; Einsiedel, Jürgen; Dürr, Maximilian; Ivanovic-Burmazovic, Ivana; Larsen, Olav; Hjorto, Gertrud Malene; Rosenkilde, Mette Marie; et al. (Journal of Medicinal Chemistry, 2016)
In this work we report a design, synthesis, and detailed functional characterization of unique strongly biased allosteric agonists of CXCR3 that contain tetrahydroisoquinoline carboxamide cores. Compound 11 (FAUC1036) is the first strongly biased allosteric agonist of CXCR3 that selectively induces weak chemotaxis and leads to receptor internalization and the β-arrestin 2 recruitment with potency comparable to that of the chemokine CXCL11 without any activation of G proteins. A subtle structural change (addition of a methoxy group, 14 (FAUC1104)) led to a contrasting biased allosteric partial agonist that activated solely G proteins, induced chemotaxis, but failed to induce receptor internalization or β-arrestin 2 recruitment. Concomitant structure-activity relationship studies indicated very steep structure-activity relationships, which steer the ligand bias between the β-arrestin 2 and G protein pathway. Overall, the information presented provides a powerful platform for further development and rational design of strongly biased allosteric agonists of CXCR3.

Identification of Two Distinct Sites for Antagonist and Biased Agonist Binding to the Human Chemokine Receptor CXCR3 - Milanos, Lampros; Saleh, Noureldin; Kling, Ralf; Kaindl, Jonas; Tschammer, Nuska; Clark, Timothy (Angewandte Chemie International Edition, 2016)
The chemokine receptor CXCR3 is a G protein-coupled receptor that conveys extracellular signals into cells by changing its conformation upon ligand binding. We previously hypothesized that small-molecule allosteric CXCR3-agonists do not bind to the same allosteric binding pocket as 8-azaquinazolinone-based negative allosteric modulators. We have now performed molecular-dynamics (MD) simulations with metadynamics enhanced sampling on the CXCR3 system to refine structures and binding modes and to predict the CXCR3-binding affinities of the biased allosteric agonist FAUC1036 and the negative allosteric modulator RAMX3. We have identified two distinct binding sites; a shallow and a second deeper pocket to which the biased allosteric agonist FAUC1036 and negative allosteric modulator RAMX3 bind, respectively.
Keywords: allosterism; membrane proteins; molecular dynamics; protein structures; signal transduction

Molecular mechanisms of biased and probe-dependent signaling at CXC-motif chemokine receptor CXCR3 induced by negative allosteric modulators - Brox, Regine; Milanos, Lampros; Saleh, Noureldin; Baumeister, Paul; Buschauer, Armin; Hofmann, Dagmar; Heinrich, Markus; Clark, Timothy; Tschammer, Nuska (Molecular Pharmacology, 2018)